Project Management Workshop : Report : Grants Scheme, Adelaide, 20-21 August 2007. - Koehler, Nicole; Payne, Tony; Harvey, Marina (Carrick Institute for Learning and Teaching in Higher Education, 2007)
Report on the outcomes of the Grants Scheme Project Management Workshop held in Adelaide in August 2007. Project team representatives, predominantly the project managers, from 48 projects attended across each of the three Grants Scheme programs, Priority Projects, Leadership and Competitive Grants. The purpose of the workshop was to provide an opportunity for project managers of Grants Scheme projects to broaden and strengthen their project management capacity and to examine common issues. Further to this, the workshop aimed to build networks and sharing between project managers. The workshop also provided an opportunity for the Carrick Institute to show support and recognise the efforts of the role of the project manager. There were varying degrees of experience across the project managers, with some projects near completion and others just beginning. The workshop demonstrated clear links and synergies between participants.